Якість і безпечність алкогольних напоїв та рекомендації щодо їх визначення - Осипенко, Олексій Панасович; Баранов, Володимир Іванович; Ковальов, Олександр Володимирович; Осипенко, Вячеслав Олексійович; Бабко, Євген Миколайович; Якобчук, Роман Леонідович (My University, 2016)
Проведено аналіз споживання алкогольних напоїв і сировини для їх виробництва. Наведено способи та методи контролю якості алкогольних напоїв і впливу мікродомішок на їх споживчі властивості. Наведено основні напрями вдосконалення виробництва алкогольних напоїв на сучасному рівні розвитку технології. The analysis of the consumption of alcoholic drinks and raw materials for their production is performed. The necessity to conduct researches concerning the influence of alcoholic drinks on a human body together with sanitation services of medicine and to consider both alcohol itself, which affects an organism, and ratio of quantitative content of micro impurity in it. It is established that for quality evaluation of drinks, it is desirable to use both traditional chemical or organoleptic control methods, and develop express train methods, objective tool methods for the determination of taste, smell and safety of drinks, which can have advisory nature for the entities. By means of sense organs: sight, sense of smell, taste it is possible to feel the impurities, which cannot be found chemically, or other methods. It is possible to assume that tasting is an objective assessment, which is necessary to use for product quality determination. This assessment commission methodically considers features of a human body to correct its mistakes. It is established that for the production, transportation, storage and consumption of alcoholic drinks, it is necessary to take into account what material the equipment, a container and packaging is manufactured from. For this purpose, it is necessary to use neutral materials despite the fact that aqueous-alcoholic solution is a good solvent of some metals, their alloys and glass. It is known that net ethanol – the basis of strong drink, does not create positive micro impurity in certain proportions render a drink bouquet. In this sense, artificial introduction of drink quantitative and high-quality additional additive into structure can create the set bouquet. This acceptance is widely used for the development of a range of drinks. The performed analysis promotes to further scientific research by the determination of influence of micro impurity in alcoholic drinks on their quality and safety.
Keywords: алкогольні напої; сировина для виробництва; якість і безпечність; дегустаційна оцінка; alcoholic drinks; materials for production; quality and safety; tasting score; кафедра машин і апаратів харчових та фармацевтичних виробництв; кафедра технологічного обладнання та комп’ютерних технологій проектування